-x+9-4=-5(x+2)

Simple and best practice solution for -x+9-4=-5(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+9-4=-5(x+2) equation:



-x+9-4=-5(x+2)
We move all terms to the left:
-x+9-4-(-5(x+2))=0
We add all the numbers together, and all the variables
-1x-(-5(x+2))+5=0
We calculate terms in parentheses: -(-5(x+2)), so:
-5(x+2)
We multiply parentheses
-5x-10
Back to the equation:
-(-5x-10)
We get rid of parentheses
-1x+5x+10+5=0
We add all the numbers together, and all the variables
4x+15=0
We move all terms containing x to the left, all other terms to the right
4x=-15
x=-15/4
x=-3+3/4

You can always share this solution

See similar equations:

| 2.8=0.9-1.9?1.9y | | x+5/3x-4=0 | | 15x-1=9x+5 | | 0=3(5c?5) | | –10v=–9v?7 | | 8+x=5x-2x | | 3k-14=(k-5)=1 | | 64-3x=73 | | 4t?8=4t?8=??3636 | | 3/x=49 | | 4t?8=4t?8=??36 | | X2+4x-9=4 | | (17^x)^3=17 | | d+10.0=92 | | | | | | 2x=(4-2) | | g+2/3=1/4? | | 34(x)=447 | | x÷1.4=2.7 | | -1=0.5*x(9) | | 34x=447 | | 125r=500 | | g-16=11 | | .-8+x=24 | | -1=0.5*x9 | | -56÷-4+19=x | | -8(g+2=-16-8g | | q÷3/7=7/10 | | q÷37=710 | | 30/(7n)=1 | | n+(n+2)*3=(n+4)*14-58 |

Equations solver categories